Factors affecting the quality of online learning in a task‐based college course - Lee, Sangmin‐Michelle (Foreign language annals, 2022)
In the face of the COVID‐19 pandemic, all colleges in Korea were forced to transition to online teaching, as was the case in most of the rest of the world. This situation engendered confusion, frustration, and dissatisfaction among students as well as instructors. The present study examined college students' perceptions of online learning in general and of one purpose‐designed course in particular and compared their responses. The objective was to identify factors that might enhance the quality of online education (OE) and learner satisfaction. The present study applied a mixed method to ensure robust results, using a survey, interviews, students' reflection papers, and the instructor's field notes. The results indicated that the students perceived online learning as less effective than traditional face‐to‐face classes overall but were satisfied with the customized online course, specifically citing the instructor's prompt feedback, interaction among students, and effective design of tasks. Given this outcome, the present study suggests several pedagogical implications for OE in the future. The Challenge What makes college students' online learning experiences satisfying? How can we provide more evidence and context to understand the effectiveness of online learning? In response to the recent publications of Gacs et al.(2020) and Hodges et al. (2020), the present study shows the qualitative differences between crisis‐prompted online courses and a planned online course during the pandemic.